Mothering queerly, queering motherhood : resisting monomaternalism in adoptive, lesbian, blended, and polygamous families - Park, Shelley M., 1961- (State University of New York Press, 2013)
Bridging the gap between feminist studies of motherhood and queer theory, this book articulates a provocative philosophy of queer kinship that need not be rooted in lesbian or gay sexual identities. Working from an interdisciplinary framework that incorporates feminist philosophy and queer, psychoanalytic, poststructuralist, and postcolonial theories, the author offers a powerful critique of an ideology she terms monomaternalism. Despite widespread cultural insistence that every child should have one - and only one - "real" mother, many contemporary family constellations do not fit this mandate. The author highlights the negative consequences of this ideology and demonstrates how families created through open adoption, same-sex parenting, divorce, and plural marriage can be sites of resistance. Drawing from personal experiences as both an adoptive and a biological mother and juxtaposing these autobiographical reflections with critical readings of cultural texts representing multi-mother families, the author advocates a new understanding of postmodern families as potentially queer coalitional assemblages held together by a mixture of affection and critical reflection premised on difference. -- Publisher's description.